2009
DOI: 10.1007/s11816-009-0092-9
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis and plant regeneration in zygotic embryo explant cultures of rugosa rose

Abstract: Rugosa rose (Rosa rugosa) is cultivated as a garden flower and an important genetic resource for the breeding of roses (R. hybrida). This study describes culture conditions for high frequency plant regeneration from zygotic embryo explants via somatic embryogenesis in rugosa rose. Mature zygotic embryo, cotyledon, and radicle explants formed embryogenic calluses at frequencies of 38, 6.7, and 8.8% when cultured on half-strength Murashige and Skoog medium (MS) supplemented with 2.26, 9.05, and 9.05 lM 2,4-dichl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…Afterwards, 2,4-D has been used as somatic embryo inducer in a broad range of species (Yu et al 2000, Puchooa 2004, Raghavan 2004. In Liliaceae, 2,4-D was reported to favor somatic embryogenesis in culture as an embryo inducer (Kim et al 2000, Mukhopadhyay et al 2004. In Iphigenia too, formation of friable, nodular and soft em-bryonic callus occurred only in presence of 2,4-D in the medium (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, 2,4-D has been used as somatic embryo inducer in a broad range of species (Yu et al 2000, Puchooa 2004, Raghavan 2004. In Liliaceae, 2,4-D was reported to favor somatic embryogenesis in culture as an embryo inducer (Kim et al 2000, Mukhopadhyay et al 2004. In Iphigenia too, formation of friable, nodular and soft em-bryonic callus occurred only in presence of 2,4-D in the medium (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Entretanto, a conversão dos calos em embriões somáticos pode ser induzida in vitro, a partir de tecidos considerados maduros, como embriões zigóticos provenientes de frutos maduros, como foi observado no presente trabalho e, também, em Lonicera japonica Thunb. (Kim et al, 2003). Resultados similares também foram alcançados por Zale et al (2004), os quais observaram que os embriões zigóticos maduros de cultivares de Triticum monococcum L. e T. tauschii (Coss.)…”
Section: Resultsunclassified
“…1B). Cells that demonstrated these characteristics were considered embryogenic cells (Durzan, 1988;Mathew and Philip, 2003;Kim et al, 2003;Sáenz et al, 2006) and staining with acetic carmine indicated the presence of reserve substances that would favor tissue development (Guerra et al, 1999). The combination of IAA and 2,4-D also promoted the development of yellowish nodules, especially in the treatments with 8.56 µM IAA plus 13.57 µM 2,4-D; 11.42 µM IAA plus 22.62 µM 2,4-D; and 14.27 µM IAA plus 22.62 µM 2,4-D. Histological analyses of this callus material revealed heavily stained cells located on the surface of the callus.…”
Section: Resultsmentioning
confidence: 99%